Eating Disorders and Obesity (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Due to the high prevalence of Eating Disorders (ED) and obesity over the life-spam and the increasing comorbidity between both conditions, the goal of this Special Issue, “Eating Disorders and Obesity: Through the Life Course”, was to approach that situation from a broader perspective. We would like to have multidisciplinary contributions, approaching ED and Obesity as potential continuum (eg. Anorexia nervosa and obesity as extreme dimensions), looking not only to shared and differential risk factors (environmental, temperamental, biological, nutritional and neuroendocrinological between ED and obesity), but also to epidemiological studies exploring transition from one to the other, through the life-course, and its impact on the treatment outcome. We were expecting to have systematic reviews and empirical studies (cross-sectional and longitudinal manuscripts), coming from all over the globe.